The Role of Institutional Ownership in Moderating the Effect of Liquidity, Capital Intensity, and Sales Growth on Tax Avoidance - Citradewi, Adelina; Ainiyah, Winda Qurotul (Disclosure: Journal of Accounting and Finance, 2025)
Tax avoidance is a legitimate tax management strategy to reduce the company's tax burden. This study aims to analyze the effect of liquidity, capital intensity, and sales growth on tax avoidance and the role of institutional ownership as a moderating variable. This study uses a quantitative approach with a descriptive method. The research sample was 37 manufacturing sector companies listed on the IDX in 2023, selected through a purposive sampling technique. Data analysis was done using multiple linear regression and moderated regression analysis (MRA) with IBM SPSS Statistics 25. The study results indicate that liquidity and sales growth do not affect tax avoidance, while capital intensity does affect tax avoidance. Institutional ownership can moderate the effect of liquidity on tax avoidance but is unable to moderate the effect of capital intensity and sales growth on tax avoidance.